The Implementation of Digital Entrepreneurship Learning in Higher Education: A Systematic Literature Review: Implementasi Pembelajaran Kewirausahaan Digital di Perguruan Tinggi: Tinjauan Pustaka yang Sistematis - Aysi, Siti Aenandari Hadatul; Susilaningsih, Susilaningsih; Sabandi, Muhammad (Universitas Muhammadiyah Sidoarjo, 2024)
The phenomenon and topic of digital entrepreneurship learning remain popular for analysis in the era of digitization. Previous literature reviews discussed the context and concept of digital entrepreneurship only. This article presents a literature review aimed at facilitating the search for research publications on digital entrepreneurship, in order to understand the track record, learning models, the impact of implementing digital entrepreneurship learning, and future research opportunities. The article has used the Systematic Literature Review (SLR) method using the Scopus database. This article has used